Iranian Scholar Haly Abbas Contributes to Europe’s First Modern Medical School - Farrokh Habibzadeh (Journal of the Pakistan Medical Association, 2025)
Medical education has not always taken place in medicalschools. Until the tenth century, medicine was taught toapprentices, or passed down from father to son. Foundedin the ninth century in Salerno, Italy, the Schola Medica Salernitanawas the first modern medical school and the mostimportant source of medical knowledge in Western Europeat the time.1 The city of Salerno was an ideal place to founda medical school: all trade routes passed through the city.Being like a melting pot of numerous cultures andethnicities, with Normans from the west, Sicilians from thesouth, Greeks, Benedictine monks, Jewish physicians, andArabs, the city was really an ideal spot to share andexchange ideas and establish a teaching center.Furthermore, the school was located near a monastery,Monte Cassino, where the sick people went to be curedwith the help of magic herbs and the miracles of the saints. Continued...